Hubungan Masa Perikatan Audit (Audit tenure) dengan Kualitas Audit: Sebuah Kajian Literatur - Azti Ainur Fani; Asti Saydatina Fedurinam; Arjun Ferandika; Fikri Rizki Utama (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to examine the relationship between audit tenure and audit quality through a literature review approach. Audit tenure is the length of the working relationship between an auditor or public accounting firm and a client company in the process of auditing financial statements. The issue of audit tenure is important because it relates to auditor independence and the effectiveness of audit implementation. The research method used is a literature review, collecting various sources such as books, scientific journals, research articles, and regulations relevant to the research topic. Data were analyzed descriptively to understand the various views and findings of previous research regarding the effect of audit tenure on audit quality. The study results indicate that long audit tenure can improve audit quality because the auditor has a deeper understanding of the company's condition and internal control system. However, a long-term relationship also has the potential to reduce auditor independence due to closeness to the client, which can affect the auditor's objectivity in providing an audit opinion. Furthermore, an auditor rotation policy is implemented as an effort to maintain auditor independence and improve audit quality. Thus, a balance is needed between the benefits of auditor experience and the importance of maintaining auditor independence to maintain audit quality.